2018
DOI: 10.1159/000481196
|View full text |Cite
|
Sign up to set email alerts
|

Slow Loris Trade in Vietnam: Exploring Diverse Knowledge and Values

Abstract: Wildlife trade can present a major threat to primate populations. In Vietnam, slow lorises (genus Nycticebus) are subject to local, regional and international demand for diverse uses including as medicine, as meat and for pets. Ethnographic approaches explore the nuances of human-primate interactions in complex sociocultural contexts. We combined ethnographic interviews of key informants with information from questionnaires, focus groups and a movie broadcast on Vietnamese television to explore diverse knowled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 58 publications
(24 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…Current methods that expand the breadth of resilience indicators available for decision-making in biocultural approaches include cultural landscape and community asset mapping, multispecies ethnographies, and the development of community well-being indicators for the conservation of biocultural landscapes (Ens 2012, Pert et al 2015, Wali et al 2017, Thạch et al 2017, McCarter et al 2018). …”
Section: Biocultural Approaches To Indicator Developmentmentioning
confidence: 99%
“…Current methods that expand the breadth of resilience indicators available for decision-making in biocultural approaches include cultural landscape and community asset mapping, multispecies ethnographies, and the development of community well-being indicators for the conservation of biocultural landscapes (Ens 2012, Pert et al 2015, Wali et al 2017, Thạch et al 2017, McCarter et al 2018). …”
Section: Biocultural Approaches To Indicator Developmentmentioning
confidence: 99%
“…Selection and outlining of second‐tier variables via iterative exploration, or a cyclical process of proposing, testing, analyzing, and refining variable choices, can be helpful to explore the dynamics and interconnections of a system across scales. For example, as we describe further below, ethnographic analysis of interviews with actors across Vietnam revealed that slow lorises are subject to opportunistic or incidental exploitation depending on cultural or socio‐economic context and location (Thạch et al, ). Thạch et al () report that while targeted trade occurs for international export of slow lorises as exotic pets at high prices through specific networks, opportunistic local exploitation varies considerably depending on local memories, customs, and beliefs regarding medicinal properties.…”
Section: Introductionmentioning
confidence: 99%
“…For example, as we describe further below, ethnographic analysis of interviews with actors across Vietnam revealed that slow lorises are subject to opportunistic or incidental exploitation depending on cultural or socio‐economic context and location (Thạch et al, ). Thạch et al () report that while targeted trade occurs for international export of slow lorises as exotic pets at high prices through specific networks, opportunistic local exploitation varies considerably depending on local memories, customs, and beliefs regarding medicinal properties. Thus, detailed exploration of variables for the study of this primate trade system that includes socio‐economic context, ethnicity, norms, and local beliefs and values can best determine how these factors interact to produce the variation seen in trade patterns at different locations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to hunting for food, other reasons for primate hunting include cultural values, particularly in some animistic societies where non‐human primates form integral parts of human mythologies or even identities. Primates may also be key ingredients in “traditional folk medicine,” especially in Asia (Alves et al, ; Starr, Nekaris, Streicher, & Leung, ; Thach et al, ; Zhou et al, ).normala.…”
Section: Introductionmentioning
confidence: 99%